Pediatric cancer testing - Schiffman, Joshua (Henry Stewart Talks, 2020)
Where cancer comes from, Genetic predisposition, hereditary cancer syndromes, and cancer genes, The questioned importance of family history, Complications of current studies and data sets, The future of genetic testing, studies, and intervention